(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article provides an analytical overview of the classical definitions and approaches to the concept of quality, its dependence on technical, economic, social, and technological characteristics, and various factors affecting quality.